A Statistical Model for Estimating the Effects of Oil Droplet Size and Oil Fraction in Microcapsules on Oxidation of Oil. Issue 12 (9th October 2017) - Miyagawa, Yayoi; Kikuchi, Kohshi; Yamamoto, Shuichi; Shiga, Hirokazu; Yoshii, Hidefumi; Adachi, Shuji
Abstract : Based on a two‐dimensional percolation theory and an autocatalytic rate expression for oil autoxidation, a statistical model is proposed to estimate the effects of the oil droplet size and the volume fraction of oil within the microcapsule on the oxidation of microencapsulated oil, by means of computational simulations. The model can address both the unique oxidation steps for microencapsulated oil: The rapid progress of oxidation at the early stage of storage and the leveling off of the oxidation after prolonged storage. The simulation also demonstrates that the reduction of the oil droplet size retards the oxidation of microencapsulated oil as well as lowering of the oil fraction within the microcapsule. Practical Applications : A statistical model is proposed to simulate oxidation process of microencapsulated oil. The simulation enable us to reasonably design oil microencapsulation. Based on a two‐dimensional percolation theory and an autocatalytic rate expression for oil autoxidation, a statistical model is proposed to estimate the effects of the oil droplet size and the volume fraction of oil within the microcapsule on the oxidation of microencapsulated oil, by means of computational simulations. Abstract : Based on a two‐dimensional percolation theory and an autocatalytic rate expression for oil autoxidation, a statistical model is proposed to estimate the effects of the oil droplet size and the volume fraction of oil within the microcapsule on the oxidation of microencapsulated oil, by means of computational simulations.